Usulan Penerapan Metode Six Sigma dalam Peningkatan Kualitas untuk Meminimasi Kecacatan Produk Kabel Nym 2 X 1.5 Mm di PT. XYZ - TitoSyahputro, Angga; Sudri, Ni Made (JITMI (Jurnal Ilmiah Teknik dan Manajemen Industri), 2025)
In the increasingly competitive industrial sector today, companies must strive to meet and maintain customer needs. PT. XYZ is a manufacturing company focused on cable production, one of which is the NYM 2 x 1.5 mm product, which has defects in its production process. To identify the factors causing product defects, a production quality control analysis is used. Six Sigma is a quality control tool that can measure the performance level of industrial systems, allowing for corrective actions to be taken. In its implementation, Six Sigma follows the DMAIC steps (Define, Measure, Analyze, and Improve). Meanwhile, FMEA (Failure Mode & Effect Analysis) is used to identify potential failures and the RPN values. Based on the analysis using the Pareto diagram, three priority defect types were identified: 21% for bulging cables, 18% for frayed cables, and 17% for rough surfaces. The FMEA results showed the highest RPN value for bulging cables due to poor material quality, for frayed cables due to machine errors, and for rough surfaces due to unstable material temperature. Recommended improvements based on the highest RPN results to reduce product defects include using lubricant on the nipple part to mitigate the effects of poor material, conducting regular machine inspections and repairs to address machine errors, and performing strict checks and tests on incoming materials to resolve unstable temperature issues.